KARAKTERISTIK PEMELAJAR PEMEROLEHAN BAHASA KEDUA: (Sebuah Studi Kasus terhadap Mahasiswa Jurusan Bahasa Jepang Universitas Negeri Jakarta) (Universitas Negeri Jakarta, 2015)
The second language acquisition that we discuss in this article refers to what Gleason and Ratner (1998 : 454) said that “we refer to second language acquisition when describing cases in which a learner who already has some degree of control over one language system is introduced to a second (or third or fourth).” The objects of this study are two students of Japanese Language Department at Jakarta State University who each of them has a very contrast characteristic. The first one is the successful one, and the other is the failure one. The purpose of this study is to see what makes them different from each other, and what makes them success or failure in the process of this second language acquisition, which is in this case is Japanese language. In this study we observed the learning strategies, personality, and their motivation of learning. As the result we found that the student with good learning strategies, which accomplished 4 main strategies in learning process, and stabil personality with high motivation will much more success than the other one.